2005
DOI: 10.2337/diabetes.54.11.3282
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Nitric Oxide Concentration in the Renal Cortex of Streptozotocin-Induced Diabetic Rats

Abstract: Nitric oxide (NO) regulates vascular tone and mitochondrial respiration. We investigated the hypothesis that there is reduced NO concentration in the renal cortex of diabetic rats that mediates reduced renal cortical blood perfusion and oxygen tension (PO 2 ). Streptozotocin-induced diabetic and control rats were injected with L-arginine followed by N-nitro-L-arginine-metyl-ester (L-NAME). NO and PO 2 were measured using microsensors, and local blood flow was recorded by laser-Doppler flowmetry. Plasma arginin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
60
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 41 publications
9
60
2
Order By: Relevance
“…These studies have confirmed some reports that have shown that plasma ADMA is elevated in insulinopenia or diabetes (19 -23), although we found normal levels in a Wistar-Furth STZ-induced diabetic model (36). They have shown further that the elevated levels can be normalized by 2 weeks of ARB administration.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…These studies have confirmed some reports that have shown that plasma ADMA is elevated in insulinopenia or diabetes (19 -23), although we found normal levels in a Wistar-Furth STZ-induced diabetic model (36). They have shown further that the elevated levels can be normalized by 2 weeks of ARB administration.…”
Section: Discussionsupporting
confidence: 80%
“…As reported in our previous studies in this STZ-induced diabetic rat model at 4 weeks (31,(33)(34)(35)(36)(37)(38), rats with diabetes had a significant decrease in body weight, an increase in blood glucose to ϳ400 mg/dl, an increase in urinary volume, and an increase in creatinine clearance without changes in mean blood pressure measured under anesthesia (Table 1). These parameters were not changed significantly by 2 weeks of telmisartan administration in both control or diabetic rats (Table 1).…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations